La ladrona de libros - Nélisse, Sophie; Rush, Geoffrey, 1951-; Watson, Emily, 1967-; Percival, Brian; Speak Up (DVD (Speak Up), 2014)
While subjected to the horrors of World War II Germany, young Liesel finds solace by stealing books and sharing them with others. In the basement of her home, a Jewish refugee is being sheltered by her adoptive parents.